Culturally disruptive research: a critical (re)engagement with research processes and teaching practices. Issue 9 (27th November 2020) - Litts, Breanne K.; Tehee, Melissa; Jenkins, Jennifer; Baggaley, Stuart; Isaacs, Devon; Hamilton, Megan M.; Yan, Lili
Abstract : Purpose: As scholars, educators and policymakers recognize the impact of partnership-based research, there is a growing need for more in-depth understanding of how to conduct this work, especially with and in diverse project teams. The purpose of this paper is to provide a critical examination of adopting a culturally disruptive approach in a research–practice partnership (RPP) that includes Indigenous and non-Indigenous researchers, designers and educators who worked together to collaboratively design culturally situated experiences for sixth graders. Design/methodology/approach: Following a design-based implementation research methodology, data from design and implementation are presented as two case studies to illustrate key findings. Findings: Leveraging the frame of culturally disruptive pedagogy, key tensions, disruptions, self-discoveries and resulting pedagogical innovations are outlined. While the authors experienced multiple forms of disruptions as researchers, designers and educators, they focused on tracing two powerful cases of how culturally disruptive research directly and immediately resulted in pedagogical innovations. Together the cases illustrate a broader shift toward interdependence that the team experienced over the course of the school year. Research limitations/implications: A new frame for conducting culturally disruptive research is presented. Both the theoretical application and practical implementation of this frame demonstrate its usefulness in conceptualizing culturally situated research through cultivating an uncomfortable yet generative interdependence. Practical implications: Findings include examples and strategies for how to practically conduct multi-sector, interdisciplinary research and teaching. Scholars and educators share their stories which illustrate the practical impact of this work. Originality/value: Critical insights presented in this paper build on and contribute to the growing body of work around RPPs, community-based research and other critical partnership methods.